EFEKTIVITAS PEMBELAJARAN MENGGUNAKAN E-BOOK MATERI FUNGSI INVERS PADA SISWA SMA NEGERI 1 TEMPUNAK - Pratiwi, Rahayu (UNIVERSITAS TANJUNGPURA, 2024)
Student achievement in learning mathematics in class X MIPA SMA Negeri 1 Tempunak is still low. This is due to the lack of use of learning media in mathematics lessons. So that the understanding of concepts, activeness, motivation and student response to the lessons delivered is less acceptable to students. So that students obtain low learning outcomes and are passive in learning. The purpose of the study was to determine the effectiveness of using e-books on inverse function material in grade X students of SMA Negeri 1 Tempunak. The subjects in this study were 22 students of grade X MIPA SMA Negeri 1 Tempunak. This study used descriptive qualitative research. The research instruments are observation sheets for learning implementation, observation sheets for student activities, response questionnaires, and learning outcome test questions. The results showed that: (1) 81.25% of learning implementation went according to what was planned in the RPP; (2) student activity obtained an overall grade point average of 85.4% and during learning students were actively involved; (3) student response questionnaires to the use of e-books in learning received positive responses with a classically average score of 77%; (4) Student learning outcomes when using e-books are categorized as good by obtaining a classical average score of 81.81% of students getting scores that exceed standard KKM scores. So that mathematics learning using e-book material on the inverse function for grade X students of SMA Negeri 1 Tempunak is effective.Keywords: Effectivenes, E-Book, Inverse Function